Time-saver standards for landscape architecture :design and construction data /coeditors, Charles W. Harris, Nicholas T. Dines ; assistant editor, Gary M. Fishbeck ; consulting editor, Albert Fein ; with a foreword by Hideo Sasaki. - Harris, Charles Wart
Includes bibliographies and index.